Les espaces résidentiels de la noblesse à Bruxelles (XVIIIe–XXe siècle) - Tatiana Debroux; Jean-Michel Decroly; Chloé Deligne; Michèle Galand; Christophe Loir; Mathieu Van Criekingen (Belgeo)
This note examines and compares the cartography of the nobility’s spaces of residence in Brussels in the late 18th century and at the very end of the 20th century. Although those spaces have been considerably expanding over the period concerned, the nobility’s contemporary spaces are definitely linked with those of the late Ancien Regime.